Pasar Tradisional dan perubahan daya hidup masyarakat pedesaan: Study Pajak Gambir Pasar VIII Desa Bandar Klippa Kecamatan Percut Sei Tuan - maswita maswita (Fakultas Hukum Universitas Al Azhar Medan, 2023)
Tax is a place to sell food and other necessities for use in daily life. The tax will continue if buyers and sellers both need it. The tax designation is different from the market designation for other areas outside North Sumatra. The purpose of this writing is to describe the changes that have occurred in the Gambir market and the lifestyle of the surrounding community. The research location is Bandar Klippa village, Percut Sei Tuan District, Deli Serdang Regency. This research uses a naturalistic approach. Focus on the strength of the ethnographic method which describes qualitatively and empirically. Data is collected from several sources, both verbally and in writing/documents, relying on involved observations and/or relatively informal conversations, data analysis using an interpretation of meaning, function, and all the consequences arising from various human actions and interaction practices in society. The traditional Gambir tax market has gradually become a place for transactions for global economic products, in addition to local economic products which continue to maintain their existence. Thus, today's traditional market culture has experienced a mixture of modern market culture through the existence of consumerist and modern products, and the lifestyle of the people around the market which tends to indulge in pleasure activities and alternative lifestyles, apart from agriculture and farming